Farmers’ livelihood, risk expectations, and homestead withdrawal policy: evidence on Jinjiang Pilot of China - Liang, Fachao; Lin, Caiyun; Lin, Sheng-Hau (International Journal of Strategic Property Management, 2022)
Although exploring the homestead withdrawal (HW) mechanism can optimize the allocation of land resource elements, the livelihood sources of farmers will change and face different sources of risk. Many studies have explored various factors affecting the HW. However, studies simultaneously exploring the relationship among farmers’ internal livelihood capital and external risk prevention capabilities and HW including differences among various HW models are still limited. The present study constructed a simple theoretical framework and used the probit model to analyze the decision-making behavior of 367 farmers in the Jinjiang Pilot in Fujian Province of China. Specifically, this study explored the impact of farmers’ livelihoods including natural, financial, and human capitals and risk expectations. Such risk expectations involve living conditions, social security, residential environment, and psychological conditions on HW in asset replacement, index replacement, and monetary compensation model. The empirical findings indicated that the farmers’ livelihoods and risk expectations have inconsistent effects on farmers’ HW decision-making in all the models, except for risk expectations. In other words, social security and residential environment have a significant inhibitory effect. These results implied that differentiated policies for HW should be considered to enhance the farmer’s sustainable livelihood capacity and controllability of risk. First published online 21 January 2022